Policy diffusion dynamics in America - Boushey, Graeme (Cambridge University Press, 2010)
"Drawing on a data set of more than 130 policy innovations, Policy Diffusion Dynamics in America demonstrates how variation in the characteristics of policies, the political and institutional traits of states, and differences among interest group carriers interact to produce different patterns of policy diffusion"--